Driving Under the Influence (of Stress) - Su, Jenny C.; Tran, Alisia G.T.T.; Wirtz, John G.; Langteau, Rita A.; Rothman, Alexander J. (Psychological Science, 2009)
Did the September 11 terrorist attacks elicit a subsequent increase in traffic fatalities? Gigerenzer (2004) argued that decreases in flying and increases in driving in the 3 months after the attacks led to 353 “surplus” traffic fatalities. We applied a more systematic analysis to the same data and found no evidence of a significant increase in miles driven or of a significant increase in traffic fatalities. However, we did find evidence for a regional effect of the attacks on driving behaviors. We hypothesized that geographic proximity to the attacks increased stress, which in turn decreased driving quality. Our analyses revealed that in the last 3 months of 2001, the Northeast exhibited a significant increase in traffic fatalities, as well as a significant increase in fatal accidents involving an alcohol- or drug-related citation. Increased stress related to physical proximity to the attacks may explain the increase in traffic fatalities.